Primary cartographic data (1670–1913) for landscape analysis of Sumy city - Tytarenko, Ihor; Pavlenko, Ivan (DataverseUA, 2026)
The study of historic urban landscapes is essential for understanding long-term spatial transformations and supporting post-war recovery strategies. When digitized and systematically organized, archival cartographic sources provide valuable insights into the evolution of urban form and serve as a robust foundation for heritage conservation and evidence-based urban planning. The dataset comprises 20 archival maps of Sumy city dating from 1670 to 1913, covering the period from the Cossack era (17th century) to the early 20th century. The materials were obtained at the authors’ request from the Department of Architecture and Urban Planning of the Sumy City Council (Sumy, Ukraine). Following high-resolution digitization, the maps were integrated into an electronic cartographic database and systematically organized within a structured data catalog. Each map is accompanied by descriptive metadata, including title, year of creation, and century classification, provided in a tabular CSV format. The dataset thus represents a coherent and FAIR-compliant collection of historical cartographic sources, enabling consistent analysis of the spatial evolution and morphological transformation of the urban landscape of Sumy city.